ANALISIS PENCATATAN DAN PELAPORAN AKUNTANSI PERSEDIAAN BARANG PADA CV. CITRA NIAGA CEMERLANG - Wani, Sri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to determine the Analysis of Recording and Accounting Reporting of Goods. The population that is used as the target of this research is the recording and inventory of goods, the data analysis used is descriptive analysis. The results showed that the implementation of the inventory recording and reporting accounting system was adequate. Within the company, there has been a clear separation of functions between the warehouse department and the inventory registering administrative staff. The selection of the method for recording inventory is also appropriate, namely by using the perpetual method, where every inventory mutation occurs will be immediately recorded in the warehouse book or inventory book. The procedures that make up the inventory recording and reporting system in this company are adequate but in practice there are sometimes procedures that are not implemented, for example the procedure for recording the cost of inventory returned to the supplier. In this procedure, the warehouse department sometimes directly asks the supplier to pick up the goods that have been sent, the goods are not in accordance with the order.